Quantification of Visco-Elastic Properties of a Matrigel for Organoid Development as a Function of Polymer Concentration - Borries, Mads; Barooji, Younes Farhangi; Yennek, Siham; Grapin-Botton, Anne; Berg-Sørensen, Kirstine; Oddershede, Lene B. (Frontiers in Physics, 2020)
The biophysical properties of polymer based gels, for instance the commonly used Matrigel, crucially depend on polymer concentration. Only certain polymer concentrations will produce a gel optimal for a specific purpose, for instance for organoid development. Hence, in order to design a polymer scaffold for a specific purpose, it is important to know which properties are optimal and to control the biophysical properties of the scaffold. Using optical tweezers, we perform a biophysical characterization of the biologically relevant Matrigel while systematically varying the polymer concentration. Using the focused laser beam we trace and spectrally analyze the thermal fluctuations of an inert tracer particle. From this, the visco-elastic properties of the Matrigel is quantified in a wide frequency range through scaling analysis of the frequency power spectrum as well as by calculating the complex shear modulus. The viscoelastic properties of the Matrigel are monitored over a timespan of seven hours. At all concentrations, the Matrigel is found to be more fluid-like just after formation and to become more solid-like during time, settling to a constant state after 1-3 hours. Also, the Matrigel is found to display increasingly more solid-like properties with increasing polymer concentration. To demonstrate the biological relevance of these results, we expand pancreatic organoids in Matrigel solutions with the same polymer concentration range and demonstrate how the polymer concentration influences organoid development. In addition to providing quantitative information about how polymer gels change visco-elastic properties as a function of polymer concentration and time, these results also serve to guide the search of novel matrices relevant for organoid development or 3D cell culturing, and to ensure reproducibility of bio-relevant Matrigels.